Flip-Book Based on Screencast-O-Matic (SoM) Video as An Asynchronous System: The Impact on University Students’ English Learning Outcomes - Husain, Balqis; Wardiman, Sri Setyarini; Abasa, Zulhasmi (The Indonesian Institute of Science and Technology Research, 2025)
This study aimed to improve students’ English skills after using a Flip-book based on Screencast-O-Matic Video as an asynchronous system. This study employed a quantitative approach that is mainly focused on true experimental research design, particularly a pre-test-post-test control group design. The population in this study was university students who studied the Economics, Civil Engineering, Environmental Engineering, Informatics Engineering, Public Administration, and Marine Science Study Program of Universitas Pasifik Morotai. At the same time, the sample was 152 university students. In this study, a simple random sampling technique was used. Mann-Whitney U test was carried out in data analysis techniques. The Kolmogorov-Smirnov test was conducted to determine the normality of the data, and a homogeneity test was implemented to determine the variance of each group. The finding demonstrated that the data was not normally distributed due to Sig. value less than 0.05 (< 0.05). Indeed, the mean Sig. value of the homogeneity test was 0.114, greater than 0.05, implying that the data was homogeneous. The Asymp value was derived from the results of the Non-parametric Mann-Whitney U test. Sig. (2-tailed) of 0.000 (< 0.05). As a result, it was reasonable to state a difference in average students’ English learning outcomes while using the Flip-book based on the Screencast-O-Matic learning model compared to conventional models. Afterward, the researchers used the N-gain interpretation with five categories to compare the effectiveness of Flip-book based on the Screencast-O-Matic Video learning model applied to the experimental group and the conventional model applied to the control group. Based on the N-Gain Score test results for the experimental group, the average value of 56.1354 or 56% fell into the quite effective category, with a minimum score of 25.00 and a maximum score of 91.30. Indeed, the N-Gain score for the control group was 21.1750, or 21 percent, when including the ineffective category, with a minimum score of -12.00 and a maximum score of 57.58. It can be concluded that the use of the Flip-book based on the Screencast-O-Matic learning model was quite effective in improving the learning outcomes of English courses for Universitas Pasifik Morotai students. In contrast, the use of conventional learning models was ineffective in improving the learning outcomes of the English courses for Universitas Pasifik Morotai students.